Not Your Lucky Day: Romantically and Numerically Special Wedding Date Divorce Risks - Jan Kabátek; David C. Ribar (Institute for the Study of Labor (IZA), 2016)
Characteristics of couples on or about their wedding day and characteristics of weddings have been shown to predict marital outcomes. Little is known, however, about how the dates of the weddings predict marriage durability. Using Dutch marriage and divorce registries from 1999-2013, this study compares the durations of marriages that began on Valentine's Day and numerically special days (dates with the same or sequential number values, e.g., 9.9.99, 1.2.03) with marriages on other dates. In the Netherlands, the incidence of weddings was 137-509% higher on special dates than ordinary dates, on an adjusted basis, and the hazard odds of divorce for special-date marriages were 18-36% higher. Sorting on couples' observable characteristics accounts for part of this increase, but even after controlling for these characteristics, special-date marriages were more vulnerable, with 11-18% higher divorce odds compared to ordinary dates. This relation is even stronger for couples who have not married before.
Keywords: J1; 330; marriage; divorce; Valentine's Day; commitment; weddings